Orai1-mediated store-operated Ca2+ entry promotes cervical cancer progression through IL-6 signaling - Pan, Yiyun; Huang, Jing; Liu, Kang; Xie, Chuanhua; Chen, Hailong; Guo, Zhong; Guo, Shoujun; Chen, Yijian (Frontiers in Molecular Biosciences, 2022)
Cervical cancer is a major cause of cancer-associated mortality among women in developing countries. Orai1-mediated store-operated Ca2+ entry (SOCE) is the primary mechanism underlying most of the non-excitable calcium influx into cells. There is at present limited evidence showing that Orai1 can function as an oncogene or a tumor suppressor depending on the cancer type. Furthermore, the exact biological functions of Orai1 in cervical cancer and the underlying mechanisms are still poorly understood. In this study, we found that Orai1 was upregulated in cervical cancer tissues, and promoted the growth of human cervical cancer cells both in vitro and in vivo. Gene silencing of Orai1 in cervical cancer cells significantly decreased interleukin (IL)-6 secretion. Interestingly, exogenous IL-6 abrogated the effects of Orai1 silencing and restored the clonogenicity of cervical cancer cells. Furthermore, we also observed a positive correlation between Orai1 and IL-6 expression in human cervical cancer samples. Taken together, our findings indicate that Orai1 functions as an oncogene in cervical cancer and is a promising therapeutic target.